Skin color variation: A study on Eastern and North East India - Maitra, Sumit; Chatterjee, Diptendu; Bandyopadhyay, Arup Ratan (Asian Journal of Medical Sciences, 2019)
Background: Skin pigmentation is one of the most variable phenotypic traits and most noticeable of human polymorphisms. Skin pigmentation in humans is largely determined by the quantity and distribution of the pigment melanin. The literature review on skin color variation revealed a few works on skin pigmentation variation has been conducted in India from Southern, Western and Northern part. Aims and Objectives: To best of the knowledge, the present discourse is the first attempt to understand skin color variation from Eastern and North Eastern part of India among three populations. Materials and Methods: The present study consisted of 312 participants from Chakma and Tripuri groups of Tripura, North East India, and participants from Bengalee Hindu caste population from West Bengal. Skin color was measured by Konica Minolta CR-10 spectrophotometer which measures and quantifies the colors with a 3D color space (CIELAB) color space created by 3 axes. All the skin color measurements from each participant were taken from unexposed (underarm) left and right to get a mean and exposed (forehead) to sunlight. Results: The distribution of skin color variation among the three populations demonstrated significant (p<0.05) difference in lightness for unexposed and exposed indicating lightness in unexposed area. Furthermore, the present study revealed significant difference (p<0.05) in skin color among the ethnic groups across the body location and all three attributes (lightness, redness and yellowness). Conclusion: Generally, skin color variation may be elucidated by two main factors: individual differences in lightness and yellowness and by and large due to ethnicity, where diversity in redness is due to primarily due to different body locations. Variation in lightness have more characteristic probability. The present study first time reports the wide range of quantitative skin color variation among the three ethnic groups from Eastern and North East India and highest yellowness (b*) among the population from North East India.